Potential Antibacterials of Merang Padi Extract (Oryza sativa) on the Growth of Gram Positive and Gram Negative Bacteria - Masniah, Masniah; Andarwati, Rini; Faisal, Ahmad Purnawarman; Wulandari, Mimin (Journal of Experimental and Clinical Pharmacy (JECP), 2023)
Padi straw (Oryza sativa) is one type of stem produced from padi tree trunks. Antibacterial activity testing was carried out by agar diffusion method using paper disc as a backup by observing the formation of a clear zone indicating the presence of antibacterial activity. Variations in the concentration of the padi straw extract test solution were made with a %w/v ratio between 100% pure padi straw extract and DMSO adjusted at various test concentrations, namely, 5%, 10%, 15%, 20%, and 25%. The results showed that the n-hexane fraction of padi straw did not have antibacterial activity because there was no inhibition zone or kill zone indicated by the fraction at both low and high concentrations. While the ethanol extract showed antibacterial activity at a concentration of 15%, the ethyl acetate fraction and the n-butanol fraction had antibacterial activity indicated by the presence of an inhibitory zone at a concentration of 7%. The results of the t-test on the ethanol extract of the test bacteria obtained a Tcount value of 14,687 which means it is very significant or very significantly different because Tcount is greater than Ttable (5% and 1%). This shows that the oxytetracycline antibiotic is better than the potency of the ethanol extract of straw on the test bacteria.